Tick paralysis in Australian birds caused by Ixodes holocyclus. Issue 12 (2nd September 2021) - Hill, AG; Clark, NJ; Tokonami, F
Abstract : Tick paralysis is an uncommon cause of neuromuscular paralysis affecting 0.12% of wild birds presented to Currumbin Wildlife Sanctuary, Queensland, with a strong seasonal predilection towards spring and summer. Clinical signs and progression of paralysis showed similarities to companion animals and were consistent across 20 species. Tick location, number of engorged ticks and number of clinical signs did not affect the outcome; however, all mortalities occurred within 4 days of admission. Treatment with canine‐derived tick antiserum resulted in clinical improvement within 24 h and a recovery rate of 73%. Average time to resolution of clinical signs was 4.3 days, with juvenile birds recovering more quickly than adults. The treatment and release of wild birds affected by tick paralysis are both achievable and rewarding, further research is required to establish treatment guidelines in birds.